2021
DOI: 10.1021/acsomega.1c02123
|View full text |Cite
|
Sign up to set email alerts
|

Study on Occluding Dentinal Tubules with a Nanosilver-Loaded Silica System In Vitro

Abstract: The effects of most clinical treatments for dentin hypersensitivity are not long-lasting. To overcome the defects, the mesoporous silica nanoparticles and silver nanoparticles entered the field of oral materials. This study aimed to synthesize a novel, lowcytotoxic dentin desensitizer and investigate its occlusion effects on dentinal tubules. The biphasic stratification approach, a chemical reduction method, and the Stober method were used to synthesize silver nanoparticle-loaded and nonporous silica-encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…External stimuli can cause fluid flow in exposed dentin tubules, stimulate sensory nerve endings, and lead to dentin hypersensitivity. Blocking dentinal tubules is the only effective way to treat tooth hypersensitivity [25]. To investigate the ability of different samples (figure 4(D-a) Water, figure 4(Db) NaF, figure 4(D-c) Hec, figure 4(D-d) SDF and figure 4(D-e) AgF@Hec) to block dentin tubules, a pH cycling test was performed.…”
Section: Morphology and Elemental Analysis Of Dental Surfacementioning
confidence: 99%
“…External stimuli can cause fluid flow in exposed dentin tubules, stimulate sensory nerve endings, and lead to dentin hypersensitivity. Blocking dentinal tubules is the only effective way to treat tooth hypersensitivity [25]. To investigate the ability of different samples (figure 4(D-a) Water, figure 4(Db) NaF, figure 4(D-c) Hec, figure 4(D-d) SDF and figure 4(D-e) AgF@Hec) to block dentin tubules, a pH cycling test was performed.…”
Section: Morphology and Elemental Analysis Of Dental Surfacementioning
confidence: 99%
“…There is an assumption that the chemical interactions between fluoride ions and free calcium ions result in calcium fluoride that can block the dentinal tubules and decrease the dentinal permeability, 15 and is partially insoluble in saliva, 13,36 and silver ions cause protein denaturation and aggregation in the dentinal tubules. 37 SEM studies have demonstrated granular precipitates in the peritubular dentin after topical application of fluorides. The traditional understanding is that, a layer of silver and dentin organic matrix protein conjugates forms when SDF is applied on sensitive dentin surfaces, which partially closes the exposed dentinal tubules.…”
Section: Mechanism Of Action Of Sdf As a Desensitisermentioning
confidence: 99%